(NpISATELX(B. (NiSKUSSTWO(B. (NwREMQ(B: [(NsTATXI I O^ERKI(B] /s (N~ASTX (B9s - (NfEDIN(B, (NkONSTANTINs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1985)
(Nw TOM WHODIT KNIGA (B"(NpISATELX(B. (NiSKUSSTWO(B. (NwREMQ(B", (NW KOTORU@ PISATELX WKL@^IL LITERATURNYE PORTRETY(B, (NSTATXI I O^ERKI RAZNYH LET(B.s
rus
Keywords: (NsTATXI I ZAMETKIs; (No^ERKI(B, (N\SSEs